Investigation of ANFIS based grid integration of DFIG using matrix converter in wind energy conversion system - Venkatasubramanian, R.; T. A. Raghavendiran, Dr. (International Journal of Engineering and Technology, 2019)
This paper offers a ANFIS control based grid integration of wind energy conversion system (WECS) through on a doubly fed induction generator (DFIG) with matrix converter. Instead of back to back converter matrix converter can be more suitable for connecting the DFIG rotor into the grid. The proposed system has been developed and simulated in MATLAB environment and analysis the system performance without rotor current controller. The DFIG and converter model has been used to calculate the performance of rotor current based on simulation results. ANFIS controller helps to reduce the error between rotor current and reference current for each of the valid states of the converter. The proposed controller has been developed a simulation in MATLAB and implemented to rotor current control for DFIG. The simulation results are analyzed and compared to with fuzzy controller. Finally, the simulation results are evaluated with IEEE 1547 standard for proving the effectiveness of the proposed system.Â Â